Osmoregulation by the Prenatal Spiny Dogfish, Squalus Acanthias - EVANS, DAVID H.; OIKARI, AIMO; KORMANIK, GREGG A.; MANSBERGER, LEIGH (Company of Biologists, 1982)
Late in gestation of the ovoviviparous dogfish, Squalus acanthias , the uterine fluids are essentially sea water, while the plasma of the pup is similar to that of the female, i.e. isotonic to sea water/uterine fluids, with significantly less Na and Cl, and substantial concentrations of urea. Early candle embryos are bathed in candle fluid and uterine fluid which contains Na and Cl concentrations intermediate between maternal plasma and sea water levels, K concentrations above sea water levels, and urea concentrations slightly below those found in the maternal plasma. Both fluids are isotonic to sea water and maternal plasma. Incubation of candles with associated embryos in sea water for 4–6 days resulted in significant increases in candle fluid Na and Cl concentrations, and a decline in candle fluid K and urea levels. However, under these conditions, the candle embryo is still able to regulate plasma Na, Cl, K and urea concentrations. The efflux of Cl is approximately 5 times the efflux of Na from the prenatal pup; however, both effluxes are equivalent to those described for adult elasmobranchs. The transepithelial electrical potential (TEP) across the pup is –4.4 mV in sea water, which indicates that both Na and Cl are maintained out of electrochemical equilibrium. Cloacal fluid flows vary diurnally with Na and Cl concentrations significantly above those of the plasma. Rectal gland efflux can account for 50–100% of the Na efflux, but less than 25% of the Cl efflux. Removal of the rectal gland resulted in an increase in plasma Na and Cl concentrations 48 or 72 h after the operation, but in both cases it appears that some extra rectal gland excretory system balances at least some of the net influx of both salts. Our results demonstrate that even very young candle embryos of S. acanthias are capable of osmoregulation, and that older embryos (pups) osmoregulate against sea water intra-utero and display the major hallmarks of elasmobranch osmoregulation, including a reduced ionic permeability ...